Immunologic Basis for Long HCDR3s in Broadly Neutralizing Antibodies Against HIV-1 - Yu, Lei; Guan, Yongjun (Frontiers in Immunology, 2014)
A large panel of potent broadly neutralizing antibodies (bnAbs) against HIV-1 has been reported in recent years, raising hope for the design of an effective vaccine based on epitopes recognized by these protective antibodies. However, many of these bnAbs contain the feature of long heavy chain complementarity-determining region 3 (HCDR3) sequences, which is viewed as an obstacle to the development of an HIV-1 vaccine targeting long HCDR3 bnAb responses. This mini-review summarizes the current literature and discusses the different potential Immunologic mechanisms for generating long HCDR3, including D-D fusion, VH replacement, long N region addition and skewed D-J genes usage, among which potential VH replacement products appear to be significant contributors. VH replacement occurs through RAG-mediated secondary recombination and contributes to the diversified naïve B cell repertoire. During VH replacement, a short stretch of nucleotides from previously rearranged VH genes is left within the newly formed HCDR3, thus elongating its length. Accumulating evidence suggests that long HCDR3s are present at significant numbers in the human mature naïve B cell repertoire and are primarily generated by recombination during B cell development. These new observations indicate that long HCDR3s, though in low frequency, are a normal feature of human antibody naïve repertoire and they appear to be selected to target conserved epitopes located in deep regions of the HIV-1 envelope trimer during HIV-1 infection. Therefore, the presence of long HCDR3 sequences should not necessarily be viewed as an obstacle to the development of an HIV-1 vaccine that promotes bnAb responses.